Development of an Android-based Computer Based Test (CBT) In Middle School - H., Nurhikmah; Gani, Hamsu Abdul; Pratama, Muh. Putra; Wijaya, Hengki (Journal of Education Technology, 2021)
The teaching and learning process, especially the process of evaluating student learning outcomes, the teacher still uses a semi-conventional evaluation process where the exam process is carried out using social media to send student exam results which are done manually on paper. This kind of evaluation process is less effective and efficient, both in terms of time, the method used, and the examination process which requires a long time and inaccurate examinations. For this reason, the authors designed a Computer Based Test (CBT) application as a media for evaluating student learning outcomes. The study aims to develop an Android-based Computer Based Test whether it is valid, practical, and effective in the learning exam / evaluation process. This research method is Research and Development which is focused on developing a smartphone-based Computer Based Test, especially Android. The development model used refers to the Alessi and Trollip development model, which consists of 3 stages, namely: planning, design, and development. The total research subjects were 30 students and 1 mathematics subject teacher. The media developed was validated by media experts and material experts, with the results of validation by material experts obtained an average score of 3.7 (very valid) and by media experts an average score of 3.8 (very valid) was obtained. This means that it can be stated that the Android-based Computer Based Test is very practical in the evaluation / exam process in mathematics subjects. Based on the results of the feasibility test of the Computer Based Test, it can be concluded that the use of the Computer Based Test is feasible to be used as a medium for evaluating learning in mathematics subjects